Data from the project "Drawings by Johan Tobias Sergel at Nationalmuseum", RAÄ-2023-2835 - Canosa, Elyse; Sandström, Tom; Slettemoen, Anne-Grethe; Hederus, Tora (Swedish National Heritage Board, 2025)
Data from the project "Drawings by Johan Tobias Sergel at Nationalmuseum" (Diarienummer RAÄ-2023-2835) including instrument reports with instrument conditions and smapling information. Data from the following analytical techniques is included: 1. X-ray fluorescence spectroscopy (XRF; data from a Bruker Artax u-XRF and Bruker Crono MA-XRF); 2. Fourier transform infrared spectroscopy (FTIR). The purpose of the project was to better understand the composition of Hetsigt Kärlekspar, a drawing by Johan Tobias Sergel (https://collection.nationalmuseum.se/en/collection/item/71030/), particularly the ink and the residual adhesive from the lining, which could perhaps lead to a better understanding of the fragile nature of the drawing and its deterioration processes.

The following collection objects were analyzed in this project:

NMH A 45/1970: Hetsigt Kärlekspar, https://collection.nationalmuseum.se/sv/collection/item/71030/

NMH 582/1875: Sergel saltar in oxtungor i Rom, https://collection.nationalmuseum.se/sv/collection/item/34944/

NMH 544/1875: Lucia, Sergels hushållerska i Rom, https://collection.nationalmuseum.se/sv/collection/item/70476/

NMH 1016/1875: Skulpturstudie, https://collection.nationalmuseum.se/sv/collection/item/70947/

NMH 518/1875 Signora Maria Sebastiani, https://collection.nationalmuseum.se/sv/collection/item/70474/

NMH 901 1875: Menelaos och Patroklos, https://collection.nationalmuseum.se/sv/collection/item/71287/

NMH 104/1906: Söker Ensligheten, https://collection.nationalmuseum.se/sv/collection/item/39545/

NMH 586/1875 Stående manlig figur, https://collection.nationalmuseum.se/sv/collection/item/70483/

NMH 47/1906 Akilles med Patrokles lik, https://collection.nationalmuseum.se/sv/collection/item/71299/
Keywords: Johan Tobias Sergel; Iron gall ink; Hetsigt Kärlekspar; XRF; FTIR; Paper conservation; Nationalmuseum; Heritage Science; RAÄ-2023-2835; Materials chemistry; History and Archaeology; Historia och arkeologi; Materials Chemistry; Materialkemi